Novel dibenzocycloheptenyl phosphonium salts as thermolatent initiator in cationic polymerization - Gupta, Mukesh Kumar; Singh, Raj Pal (Journal of Applied Polymer Science, 2009)
In this study, novel thermolatent cationic initiators based on dibenzocycloheptenyl phosphonium salts (1a, 1b, 1c, 1d, 2a, and 3a) were synthesized and their efficiency was examined in bulk polymerization of glycidyl phenyl ether (GPE). The polymerization of GPE was performed with 1 mol % of dibenzocycloheptenyl triphenylphosphonium salts (1a-1d) with different counter anions (SbF(6)(-), PF(6)(-), AsF(6)(-), and BF(4)(-)) at 25-200 degrees C for 1 h. The order of initiator activity was found as 1a > 1d > 1b > 1c. To examine the effect of phosphine moiety, the activity of la was compared with dibenzocycloheptenyl-tri-n-butylphosphonium hexafluoroantimonate (2a). The order of initiator activity was observed as 1a > 2a. The initiator activity of la was compared with that of 10,11-dihydro-dibenzocycloheptenyltriphenylphosphonium hexafluoroantimonate (3a) to understand the effect of extended conjugation in dibenzocycloheptenyl ring. In general, with the increase in the polymerization temperature, conversion (%) also increases. The solubility of initiators in various solvents and epoxy monomers was also examined. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 112: 3707-3713, 2009
Keywords: Cationic polymerization; glycidyl phenyl ether; initiators; phosphonium salt; thermolatent